Opportunity cost of mega infrastructure projects in Africa: Should development be traded for growth? Evidence from Tanzania - Harold M.L. Utouh; Felician Andrew Kitole (Cogent Economics & Finance)
Mega infrastructure projects are important for driving economic growth and development across nations, yet their impacts are often uneven, particularly in developing countries like Tanzania, where they leave vulnerable populations exposed to socio-economic challenges. This study examines the dynamics of mega infrastructure projects using Likert scale, Structural Equation Modeling and Two-Stage Least Squares to assess perceptions, economic impacts and trade-offs using data sampled from 350 respondents. The findings reveal that while these projects boost income per capita, asset ownership and business ownership, they negatively affect quality of life, access to services and literacy rates. Moreover, correlation analysis confirms a negative relationship between economic growth and development, indicating a trade-off where gains in one area may lead to losses in another. The study recommends enhancing public participation through structured engagement mechanisms, ensuring equitable resource allocation by mandating dedicated social investments, integrating sustainability principles through comprehensive impact assessments and establishing strong monitoring frameworks to track both economic and socio-economic outcomes. These strategies are crucial not only for Tanzania but also for other developing nations, where balancing rapid economic growth with inclusive and sustainable development is essential to ensuring that infrastructure projects benefit all communities equitably and leave no population behind.